Assessment of the need for cardiovascular risk factor prevention among organized populations of intellectual workers - A. V. Kontsevaya; A. M. Kalinina; T. S. Romanenko; M. G. Omelyanenko; A. I. Popugaev; S. V. Belonosova; Yu. M. Pozdnyakov; M. B. Khudyakov (Кардиоваскулярная терапия и профилактика)
One of the conditions for high-quality medical care, including medical prevention, is preliminary assessment of objective need for this type of medical service.Aim. То assess the need for medical prevention of cardiovascular risk factors (CVD RFs) in organized collectives of educational and research workers. То identifY preventive behavior models requiring different tactics for individual preventive programs.Material and methods. А survey was performed in two collectives of intellectual workers, to assess their need for CVD RF prevention and identify preventive behavior models as а basis for individual preventive programs.Results. Among the collectives exarnined, both CVD RF prevalence and unmet need for CVD RF coпection were high; the latter reached 70-80 % among all individuals with RFs.Conclusion. The indicators of preventive consulting need could Ье used for developing targeted preventive programs.